Influence of Treating Essential Oils of Canarium Tree Resin on The Level Malondialdehyde (MDA), Protease Activity, Bronchi Histopathology Description and Expression of Tumor Necrosis Alpha Factor (TNF-α) on Asthma Rats (Rattus norvegicus) - Faijal Fachrudin Mbabho; Aulanni’am Aulanni’am; Arie Srihardyastutie (The Journal of Pure and Applied Chemistry Research, 2018)
Essential oils of canarium tree resin (Canarium indicum L) have anti-inflammatory and antioxidant activity. Inflammation of the bronchi and airway remodeling is a major factor in the occurrence of asthma. The purpose of this study was to study the potential of essential oils of canarium tree resin on the expression of TNF-α, changes in bronchial epithelial cell features, MDA levels and protease activity from OVA and LPS exposure in a rat model of asthma. This study used four groups of rat, the negative control group, asthma group, therapy group dose 25 mg/kg BB and 50 mg/kg BB. TNF-α expression was calculated using Walter calculations, histopathologic observation of bronchi was observed using Olympus BX51 microscope, MDA level was measured using Thiobarbituric Acid (TBA) method and measurement of protease activity was done by spectrophotometric method, and analyzed by ANOVA. The results showed that the therapy of essential oils of canarium tree resin at 25 mg/kg BB and 50 mg/kg BB significantly (P<0.05), after treatment for seven days decreased, MDA 44%, Protease activity 46%, improved bronchial epithelium and TNF-α expression by 51%. This study proves that essential oils of canarium tree resin can be effectively used as therapy in asthma model rats.